Assessing Mutatis Mutandis’ Authorities of Sabang Free Trade and Free Port Zone within the Indonesian Law on Job Creation - Zharfan, Ahmad; Aiyub Kadir, M. Yakub (Media Syari'ah, 2023)
This paper discusses authorities of Sabang Free Trade and Free Port Zone(KPBPB) and its dilemma post the existence of the Law on Job Creation (UU-Cipta Kerja) and Constitutional Court decision, in terms of ‘Mutatis Mutandis’ in attracting investment.  There is conflict regulation after the government issued UU-Cipta Kerja, including facilities and conveniences in the form of entry and exit of goods, taxation, customs, excise and licence. The application of Online Single Submission(OSS) system has centralized the authority while KPBPB Sabang to become only a beneficiary. Hence the Application of ‘Mutatis Mutandis’ to   necessary changes for attracting Investment opportunities is required. This paper contributes to clarify the authority of KPBPB Sabang in terms of  strengthening  and repositioning the KPBPB within centralization notion of Job creation law.